Renal and Cardiovascular Morbidities Associated with APOL1 Status among African-American and Non-African-American Children with Focal Segmental Glomerulosclerosis - Woroniecki, Robert P.; Ng, Derek K.; Limou, Sophie; Winkler, Cheryl A.; Reidy, Kimberly J.; Mitsnefes, Mark; Sampson, Matthew G.; Wong, Craig S.; Warady, Bradley A.; Furth, Susan L.; Kopp, Jeffrey B.; Kaskel, Frederick J. (Frontiers in Pediatrics, 2016)
Background and objectives: African American (AA) children with focal segmental glomerulosclerosis (FSGS) have later onset disease that progresses more rapidly than in non-AA children. It is unclear how APOL1 genotypes contribute to kidney disease risk, progression and cardiovascular morbidity in children. Design, setting, participants, & measurements: We examined the prevalence of APOL1 genotypes and associated cardiovascular phenotypes among children with FSGS in the Chronic Kidney Disease in Children (CKiD) study; an ongoing multicenter prospective cohort study of children aged 1-16 years with mild to moderate kidney disease. Results: A total of 140 AA children in the CKiD study were genotyped. HR APOL1 genotypes were present in 24% of AA children (33/140) and were associated with FSGS, p<0.001. FSGS was the most common cause of glomerular disease in children with HR APOL1 (89%; 25/28). Of 32 AA children with FSGS, 25 (78%) had HR APOL1. Compared to children with low risk (LR) APOL1 and FSGS (comprising 36 non-AA and 7 AA), children with HR APOL1 developed FSGS at a later age, 12.0 (IQR: 9.5, 12.5) vs 5.5 (2.5, 11.5) years, p=0.004, had a higher prevalence of uncontrolled hypertension (52% vs 33%, p=0.13), left ventricular hypertrophy (53% vs 12%, p<0.01), C-reactive protein > 3 mg/L (33% vs. 15%, p=0.12) and obesity (48% vs. 19%, p=0.01). There were no differences in glomerular filtration rate, hemoglobin, iPTH, or calcium-phosphate product. Conclusions: AA children with HR APOL1 genotype and FSGS have increase prevalence of obesity and LVH despite a later age of FSGS onset, while adjusting for socioeconomic status. Treatment of obesity may be an important component of CKD and LVH management in this population.